A New Method for Removal of Hydrogen Peroxide Interference in the Analysis of Chemical Oxygen Demand - Wu, Tingting; Englehardt, James D (Environmental science & technology, 2012)
Many advanced oxidation processes involve addition of hydrogen peroxide (H2O2) with the aim of generating hydroxyl radicals to oxidize organic contaminants in water. However, chemical oxygen demand, a common measure of gross residual organic contamination, is subject to interference from residual H2O2 in the treated water. A new method, involving catalytic decomposition of H2O2 with addition of heat and sodium carbonate (Na2CO3), is proposed in this work to address this problem. The method is demonstrated experimentally, and modeled kinetically. Results for 5 mM H2O2 in deionized (DI) water included reduction to below the COD detection limit after 60 min heating (90◦C) with addition of 20 g/L Na2CO3 concentrated solution, whereas 900 min were required in treated municipal wastewater. An approximate second order rate constant of 11.331 M–1·min–1 at Na2CO3 dosage of 20 g/L was found for the tested wastewater. However, kinetic modeling indicated a two-step reaction mechanism, with formation of peroxocarbonate (CO4 2‑) and ultimate decomposition to H2O and O2 in pure H2O2 solution. A similar mechanism is apparent in wastewater at high catalyst concentrations, whereas at low Na2CO3 addition rates, the catalytic effects of other constituents appear important.